“FEEDBACK CATACLYSM” & THE JOHARI WINDOW - Manoj Krishnan C.G (REVIEW OF SOCIAL SCIENCES, 2014)
Feedback plays a very effective role in organizations by acting as a reason for organizational existence. Bringing in continuous and sustained success to business organizations, and to transform the organizations as learning one is made possible only by improving the capabilities of individuals in organizations. Here comes the role of giving effective feedback. But, the question is to what extent is a manager ethical in giving feedback and giving feedback has become a mere exercise which no one cares for. Reasons are many, but work place suffers from this. We can call this condition as Feedback Cataclysm. We first learned about the concept of Johari Window in our organizational behavior classes during the M.B.A course and it piqued our interest. Self awareness makes you understand the other person in a better manner which further helps you to share information and connect with others. The concept has its origin from the pioneering works of Joseph Luft and Harry Ingham in 1955, developing this conceptas a tool to help people understand their interpersonal communication and relationships.